Les leviers agricoles d’une pensée paysagère de l’urbanisme - Emmanuelle Bonneau (Projets de Paysage)
Currently landscape architects are considered as legitimate stakeholders in the development of urban planning projects focused on the valorization of agricultural spaces and the environment. Based on the practical experience of the Atelier Arcadie (Emmanuel Prieur is a certified landscape architect based in Bordeaux), this article takes a look at a new approach to the landscape and urban planning in which agriculture, as a space, an economic activity and a form of development is a driver.